Upper digestive hemorrhage secondary to major duodenal papilla Dieulafoy’s lesion: Case report (Research, Society and Development, 2021)
Introduction: Dieulafoy’s lesion (DL) is occasioned by a tortuous, persistent and large caliber artery that emerges the mucosa from the submucosa of an organ, eventually triggering gastrointestinal bleeding in the presence of eroding factors of the mucosa and arterial wall. The presence of DL has been described in many anatomic topographies and although it predominates in the upper digestive tract, the presence of this lesion exactly in the major duodenal papilla is a rare event. Objective: to report a case of upper gastrointestinal bleeding secondary to a major duodenal papilla DL. Case report: a 72 year-old female, admitted to hospital care with a clinical history of two months continuous, painless melena, multiple previous blood transfusions and symptomatic anemia. She was referred by another health service with the diagnostic hypothesis of hemobilia, suggested by two previous esophagogastroduodenoscopies. Her abdominal ultrasound and arteriography were normal. A third esophagogastroduodenoscopy evidenced active bleeding in the duodenal major papilla, and after a carefully analysis a papillar DL was diagnosed. It was treated by endoscopy with adrenaline 1:10000 injection and thermocoagulation. Following this procedure she evolved with severe acute pancreatitis due to papillitis and need of intensive care unit admission. No rebleeding was detected and hospitalar discharge occurred twenty days after hospitalization. Conclusion: The localization of a DL at the major papilla is a rare event and acute pancreatitis is a complication related to its endoscopic treatment.